Use of Recurrence Quantification Analysis to Examine Associations Between Changes in Text Structure Across an Expressive Writing Intervention and Reductions in Distress Symptoms in Women With Breast Cancer - Lyby, Marlene Skovgaard; Mehlsen, Mimi; Jensen, Anders Bonde; Bovbjerg, Dana Howard; Philipsen, Johanne S.; Wallot, Sebastian (Frontiers in Applied Mathematics and Statistics, 2019)
The current study presents an exploratory analysis of using Recurrence Quantification Analysis (RQA) to analyze text data from an Expressive Writing Intervention (EWI) for Danish women treated for Breast Cancer. The analyses are based on the analysis of essays from a subsample with the average age 54.6 years (SD = 9.0), who completed questionnaires for cancer-related distress (IES) and depression symptoms (BDI-SF). The results show a significant association between an increase in recurrent patterns of text structure from first to last writing session and a decrease in cancer-related distress at three months post-intervention. Furthermore, the change in structure from first to last essay displayed a moderate, but significant correlation with change in cancer-related distress from baseline to nine months post-intervention. The results suggest that changes in recurrence patterns of text structure might be an indicator of cognitive restructuring that leads to amelioration of cancer-specific distress.